Upaya Peningkatan Motivasi Belajar Siswa Kelas XI dengan Pembelajaran Full Day School di Jurusan Teknik Kendaraan Ringan Otomotif dan Teknologi Bisnis Sepeda Motor di SMK N 1 Bukittinggi - Dicky Auranda Putra; Martias Martias (Lembaga Yasin AlSys, 2026)
Research on the implementation of the Full Day School system in vocational education has been widely conducted, yet studies that specifically highlight its role in enhancing students’ learning motivation in automotive programs remain relatively limited. This study aimed to evaluate the effectiveness of Full Day School instruction in improving the learning motivation of Grade XI students in the Light Vehicle Automotive Engineering and Motorcycle Business Technology programs at SMK Negeri 1 Bukittinggi. A quantitative approach was employed using a Classroom Action Research (CAR) design based on Kurt Lewin’s model, comprising the stages of planning, action implementation, observation, and reflection, with 60 students selected through total sampling as the research subjects. Data were collected through observations and Likert-scale learning motivation questionnaires, then analyzed using descriptive quantitative techniques with percentage calculations. The findings show a significant increase in students’ learning motivation following the implementation of Full Day School instruction, as indicated by a shift in motivation categories from low at the pre-cycle stage to good and very good across the action cycles. These results contribute to the development of learning motivation concepts in vocational education and broaden understanding of Full Day School implementation in vocational high schools. The study concludes that structured, varied, and learner-oriented management of instruction within a Full Day School system is crucial for enhancing learning motivation, with practical implications for teachers and schools in designing more effective instructional strategies and opening avenues for further research on the impact of Full Day School on other affective and academic aspects.